Effect of thoracolumbar fascia injury on reported outcomes after percutaneous vertebroplasty - Yang, Songbo; Tang, Jie; Yang, Zhaoyi; Jin, Hongju; Wang, Qinglei; Wang, Huiming (Frontiers in Surgery, 2024)
Purpose: Thoracolumbar fascia injury is often associated with poor early pain relief after percutaneous vertebroplasty (PVP). This study will evaluate the effects of thoracolumbar fascia injury on early pain relief and time to get out of bed after PVP.Methods: A total of 132 patients treated with PVP for osteoporotic vertebral compression fractures (OVCF) were included and divided into injured group (52 cases) and non-injured group (80 cases) according to the existence of thoracolumbar fascia injury. Before surgery, 1 day, 3 days, 1 week, 1 month, and 3 months after surgery, and at the last follow-up, the primary patient-reported outcome measures (PROMs) were the visual analogue scale (VAS) of pain while rolling over and standing, and the secondary PROMs was the Oswestry disability index (ODI). Meanwhile, the achieved rate of minimal clinically important differences (MCID) and patient acceptable symptom states (PASS) of the above measures in both groups was evaluated at the last follow-up.Results: Except for the postoperative 3 months and the last follow-up, there were statistically significant differences in VAS-standing and ODI between the two groups at other time points after surgery (P < 0.05), and the non-injured group was significantly better than the injured group. At the last follow-up, there was no statistically significant difference in the MCID and PASS achievement rates of the above measures between the two groups (P>0.05). In addition, the proportion of patients who got out of bed 1 and 3 days after surgery in the non-injury group was significantly higher than that in the injury group (P=0.000 for both). poor pain relief in the early stage 删除[webuser]: Conclusion: Thoracolumbar fascia injury significantly affected early pain relief and extended time of getting out of bed after PVP. Attention should be paid to preoperative evaluation of thoracolumbar fascial injury in order to better predict the postoperative efficacy of PVP. .